2022
DOI: 10.1007/s11356-022-21474-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different salt solutions for density separation of conventional and biodegradable microplastic from solid sample matrices

Abstract: Microplastics are the new emerging pollutants ubiquitously detectable in aquatic and terrestrial ecosystems. Fate and behavior, as well as ecotoxicity, are of increasing environmental concern, particularly in sediments and soils as natural sinks. For a global environmental risk assessment, reliable and easy to apply analytical methods are mandatory to obtain comparable data. This is based on the isolation of microplastics out of the solid sample matrices prior to instrumental detection. Thus, this study provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Digestions were performed on shaker tables set to 175 revolutions/min in a fume hood for 24 h. Samples were then returned to a drying oven set to 65 °C to remove residual H 2 O 2 . Samples were rehydrated with 100 mL of 905 g NaBr/L H 2 O (ρ = 1.53 g/cm 3 ), and a stir bar was added to each beaker (Radford et al, 2021;Schutze et al, 2022). Sodium bromide was used over other common salt solutions (NaCl, ZnCl 2 ) because of its ability to separate out higher-density plastics such as polyester (ρ = 1.24-1.40 g/cm 3 ) and polyvinyl chloride (ρ = 1.29-1.44 g/cm 3 ; Radford et al, 2021).…”
Section: Microplastic Isolationmentioning
confidence: 99%
“…Digestions were performed on shaker tables set to 175 revolutions/min in a fume hood for 24 h. Samples were then returned to a drying oven set to 65 °C to remove residual H 2 O 2 . Samples were rehydrated with 100 mL of 905 g NaBr/L H 2 O (ρ = 1.53 g/cm 3 ), and a stir bar was added to each beaker (Radford et al, 2021;Schutze et al, 2022). Sodium bromide was used over other common salt solutions (NaCl, ZnCl 2 ) because of its ability to separate out higher-density plastics such as polyester (ρ = 1.24-1.40 g/cm 3 ) and polyvinyl chloride (ρ = 1.29-1.44 g/cm 3 ; Radford et al, 2021).…”
Section: Microplastic Isolationmentioning
confidence: 99%
“…The dried sediment was then pulverized using a mortar and pestle. Furthermore, the density separation stage by mixing a saturated NaCl solution as much as 3 times the weight of the sediment into the sediment, then stirring for 2 minutes (Rani et al, 2023;Schütze et al, 2022). After stirring the sediment sample bath is allowed to stand for 1 hour, the light plastic will separate and will be at the top.…”
Section: Isolation Of Microplasticsmentioning
confidence: 99%
“…Saturated NaCl solution was used as the density separation solution as it is a more economical and practical approach; higher density solutions are usually expensive and are not cost-efficient for the sole purpose of preparing 'clean' beach sediments. On the other hand, Method 2 involved subjecting the beach sediments in aluminum pans to a furnace at 550°C for 4 h (Schütze et al, 2022). Lastly, Method 3 employed a density separation method using saturated NaCl (single extraction) followed by subjecting the beach sediments to a furnace at 550°C for 4 hours (Shim et al, 2016), as shown in Figure 2.…”
Section: Preparation Of Sediments For Controlsmentioning
confidence: 99%
“…However, obtaining a reference material in the form of 'clean' beach sediments is very difficult and not commercially plausible (Silva et al, 2018;Cadiou et al, 2020). While some studies have employed their own protocol for 'cleaning' beach sediments (Shim et al, 2016;Bridson et al, 2020;Schütze et al, 2022), no controlled comparisons have yet been made that can inform future harmonization efforts. Thus, there is a need to optimize towards an efficient method for removing plastic contamination in beach sediments.…”
Section: Preparation Of Sediments For Controlsmentioning
confidence: 99%